Real-Time Monitoring of Ascorbic Acid-Mediated Reduction of Cytotoxic Effects of Analgesics and NSAIDs on Tenocytes Proliferation - Chih-Hao Chiu; Poyu Chen; Alvin Chao-Yu Chen; Yi-Sheng Chan; Kuo-Yao Hsu; Higashikawa Rei; Kin Fong Lei (SAGE Publishing, 2019)
Tendinopathy is a common painful musculoskeletal disorder treated by injection of analgesics and nonsteroidal anti-inflammatory drugs (NSAIDs), which are believed to have cytotoxicity toward tenocytes. Ascorbic acid is an antioxidant that promotes collagen biosynthesis and prevents free radical formation. It is believed to protect tenocytes from oxidative stress. The optimal concentration of ascorbic acid, especially when used in conjunction with anesthetics and NSAIDs injection, to treat different stages of tendinopathies is unknown. Human tenocytes were isolated from a torn edge of the supraspinatus tendon of a 51-year-old male patient during arthroscopic repair. We monitored real-time changes in human tenocyte proliferation upon exposure to different concentrations of ascorbic acid, bupivacaine, and ketorolac tromethamine using the xCELLigence system. No significant changes in cell index were observed between the control group and tenocytes treated with the 3 concentrations of ascorbic acid. Tenocytes exposed to 0.5% bupivacaine and 30 or 15 mg/mL ketorolac tromethamine revealed significant reduction in tenocytes proliferation. Bupivacaine 0.5% with 250 μg/mL ascorbic acid and 15 mg/mL ketorolac tromethamine with 250 μg/mL ascorbic acid showed the least cytotoxicity against tenocytes. The optimal ascorbic acid concentration required to reduce the cytotoxic effects of bupivacaine and ketorolac tromethamine was demonstrated using this platform.